LCZ696, an angiotensin receptor-neprilysin inhibitor, ameliorates epithelial-mesenchymal transition of peritoneal mesothelial cells and M2 macrophage polarization - Yan Hu; Canxin Zhou; Qin Zhong; Xialin Li; Jinqing Li; Yingfeng Shi; Xiaoyan Ma; Daofang Jiang; Yi Wang; Shougang Zhuang; Na Liu (Renal Failure)
Aims To investigate the effects and mechanisms of LCZ696, an angiotensin receptor-neprilysin inhibitor (ARNI), on epithelial-mesenchymal transition (EMT) of peritoneal mesothelial cells and on macrophage M2 polarization.Methods We examined the effects of LCZ696 in a 4.25% high glucose peritoneal dialysis fluid (PDF)-induced peritoneal fibrosis (PF) mouse model, and explored the mechanisms of LCZ696 on human peritoneal mesothelial cells (HPMCs) stimulated by TGF-β1 (5 ng/mL) and on Raw264.7 cells stimulated by IL-4 (10 ng/mL). To further elucidate the mechanism, we treated HPMCs with the conditioned medium of Raw264.7 cells.Results LCZ696 effectively improved PF and inhibited the process of EMT in PDF mice. In vitro, LCZ696 also significantly alleviated the EMT of TGF-β1 induced HPMCs, although there was no statistically significant difference when compared to the Valsartan treatment group. Moreover, LCZ696 ameliorates the increased expression of Snail and Slug, two nuclear transcription factors that drive the EMT. Mechanistically, TGF-β1 increased the expression of TGFβRI, p-Smad3, p-PDGFRβ and p-EGFR, while treatment with LCZ696 abrogated the activation of TGF-β/Smad3, PDGFRβ and EGFR signaling pathways. Additionally, exposure of Raw264.7 to IL-4 results in increasing expression of Arginase-1, CD163 and p-STAT6. Treatment with LCZ696 inhibited IL-4-elicited M2 macrophage polarization by inactivating the STAT6 signaling pathway. Furthermore, we observed that LCZ696 inhibits EMT by blocking TGF-β1 secretion from M2 macrophages.Conclusion Our study demonstrated that LCZ696 improves PF and ameliorates TGF-β1-induced EMT of HPMCs by blocking TGF-β/Smad3, PDGFRβ and EGFR pathways. Meanwhile, LCZ696 also inhibits M2 macrophage polarization by regulating STAT6 pathway.